Hi everyone,
0.45 = (a - x(bcd + bce + bf)) / (a + x(bcg - bcd -bce -bf))
x = ?
I'm stuck and I need help! (I'm a 56 yo guy and school classes are very far...)
Thanks!
The appearance seems a bit pointless. Can you solve \(\displaystyle 0.45 = \dfrac{a - xH}{a+x(J-H)}\), for x?
Ahh, I do not think it pointless at all. Finding the relatively simple in the seemingly complex is one of the skills that math teaches you.The appearance seems a bit pointless. Can you solve \(\displaystyle 0.45 = \dfrac{a - xH}{a+x(J-H)}\), for x?
Which obviously entails that it cannot be pointless.Well, Sir Vindiou he no seem too interested...edited his post to a point!!
Since you're solving for x, then the rest is assumed to be givens; so simplify:0.45 = (a - x(bcd + bce + bf)) / (a + x(bcg - bcd -bce -bf))
x = ?